2013
DOI: 10.1186/1475-2891-12-42
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of nutritional status using malnutrition universal screening tool in patients with pulmonary tuberculosis

Abstract: BackgroundMalnutrition is frequently observed in patients with pulmonary tuberculosis (TB). The present study aimed to examine the relationship between nutritional status using Malnutrition Universal Screening Tool (MUST) and the mortality of patients with pulmonary TB.MethodsFifty-seven patients with pulmonary TB were analyzed. Nutrition assessment was carried out using MUST. The Cox proportional hazard model was applied to assess the ability of MUST to predict prognosis. Receiver operating characteristic cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 16 publications
1
29
0
3
Order By: Relevance
“…Several studies reported that patients with active pulmonary tuberculosis are under or malnourished. 41,42 It is further reported that age as well as nutritional status significantly influences the isoniazid acetylator status as well as drug levels in tuberculosis subjects. 30 Hence, nutritional support is needed for undernourished tuberculosis subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that patients with active pulmonary tuberculosis are under or malnourished. 41,42 It is further reported that age as well as nutritional status significantly influences the isoniazid acetylator status as well as drug levels in tuberculosis subjects. 30 Hence, nutritional support is needed for undernourished tuberculosis subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional status has been shown to be a predictor of outcomes for some pulmonary diseases such as chronic obstructive pulmonary disease (COPD) [7] or tuberculosis [8]. For these diseases, an unbalanced nutritional status is associated with a poorer outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Este achado sugere que a alimentação de pacientes com TB pulmonar apresentava possíveis deficiências nutricionais, as quais podem gerar implicações no processo de tratamento e recuperação do estado de saúde. 4 Em relação às variáveis sociodemográficas, os resultados demonstram o predomínio da TB pulmonar em pacientes do sexo masculino (62,2%), concordante com outros estudos, tendo em vista a maior exposição a fatores de risco, menor procura pelos serviços de saúde e aos hábitos culturais relacionados ao comportamento masculino em situações de adoecimento.…”
Section: Discussionunclassified
“…3 A relação entre TB pulmonar e nutrição tem sido apontada como um aspecto importante para a efetividade da resposta imunológica do hospedeiro à doença. 4 Na medida em que pode ocorrer o catabolismo proteico, ativação de citocinas e modificações no sistema imune e trato gastrointestinal, ocasionando a desnutrição e/ou carências nutricionais. 5 A desnutrição constitui importante indicador quanto ao risco de contrair a TB e pode também influenciar na eficiência do tratamento, considerando que a administração dos medicamentos padronizados pode provocar efeitos adversos, entre eles alterações hepáticas e gastrointestinais.…”
unclassified